Develoment of monitoring system using IoT for stand-alone hydrokinetic energy harnessing - Nurfarizathul Akma, Roslan (2022)
In this thesis, the development of Io T system for stand-alone hydrokinetic energy harnessing is presented the hydrokinetic technology can provide 24 hours electricity as long as the river is flowing. The design of the stand-alone hydrokinetic energy harnessing that is capable from 220V AC to l 2V DC will create the opportunity to harvest energy using waterflow or hydrokinetic energy. Although hydrokinetic technology is one of the best options for supplying electricity in remote areas near rivers, several issues must be considered, including low water velocity and shallow water depth. The circuit is design is also to convert AC signal to DC signal to the load from the water flow velocity. The methods chosen to have been scrutinised in every detail to ensure a satisfactory result of the performance energy harvesting. The Maximum Power Point Tracking (MPPT) algorithm is intended to track and control water flow due to pattern and variation, non-linear water velocity, and slow tracking response. A monitoring system is also designed to check the power and current values in the hydrokinetic energy harnessing. As a result, improvements to this mechanism will be implemented in rural areas. This project proposes the use of a hydrokinetic turbine, which is a crossflow water turbine. At the end of this project, several tests were performed to demonstrate that the electricity generated by the turbines is sufficient to power a sufficient number of low-power appliances.